INT-008 Comparison of pharmacist-led medication review at different stages during the inpatient stay. (24th February 2014) - Graabæk, T; Knudsen, T; Clemmensen, MH; Aagaard, L
Abstract : Background: 5–30% of all acute admissions are caused by medication-related problems, of which many are preventable. In Denmark clinical pharmacists perform medication review both at admission and later in the inpatient stay, but no study has compared the clinical pharmacist interventions at different stages of the hospital journey. Purpose: The aim of this study is to compare interventions from pharmacist-led medication review at admission and during hospital stay among elderly patients. Methods: A randomised intervention study was performed from April to September 2013. 120 acutely admitted medical patients' * 65 years of age were equally randomised to "control", "ED" or "STAY" groups. The "control" group received standard care, the "ED" group received medication review and patient interview at admission and the "STAY" group received medication review and patient interview at admission plus medication review during hospital stay. Patient characteristics and process data for the interventions was recorded. Results: 163 patients were invited to participate, whereof 43 patients declined. 120 patients with a mean age of 76 years, 51% male and a mean of 7.6 medications were included. On the emergency department, the pharmacist identified 162 medication-related problems in 73 of the 80 "ED" + "STAY" patients, used 28 min per identified problem and achieved an acceptance rate of 54%. During inpatient stay medication review was performed for 16 of the 40 "STAY" patients, primarily because more than half of the patients were discharged directly from the emergency department. The pharmacist identified 24 medication-related problems in 14 of the 16 "STAY" patients, used 18 min per identified problem and achieved an acceptance rate of 82%. Conclusions: The findings indicate the importance of pharmacist-led medication review during the entire hospital journey, because even though medication-related problems were solved at admission, the main part of the patients presented new problems later in the inpatient stay. No conflict of interest.